Bredemolic Acid Ameliorates Selected Liver Function Biomarkers in a Diet-Induced Prediabetic Rat Model - Akinjide Moses Akinnuga; Angezwa Siboto; Bongiwe Khumalo; Ntethelelo Hopewell Sibiya; Phikelelani Ngubane; Andile Khathi (Canadian Journal of Gastroenterology and Hepatology)
Background. Prediabetes is an intermediary hyperglycaemic state that precedes type 2 diabetes mellitus (T2DM) in which abnormal metabolism of glucose and lipids occurs in organs such as the liver. Evidence has shown that, about 70% of T2DM patients develop hepatic dysfunction which is found to begin during the prediabetic stage. Bredemolic acid, a pentacyclic triterpene, has been found to improve insulin sensitivity in diet-induced prediabetic rats. The effects of this compound on liver function, however, are unknown. This study was therefore designed to investigate the effects of BA on liver function in high fat-high carbohydrate (HFHC) diet-induced prediabetic rats. Methods. Thirty-six (36) male rats that weigh 150 g–180 g were divided into two groups, the non-prediabetic (n = 6) and the prediabetic groups (n = 30) that were fed normal diet (ND) and HFHC diet, respectively. The prediabetic rats were further subdivided into five groups (n = 6) and treated with either BA (80 mg/kg) or metformin (MET, 500 mg/kg) every third day for 12 weeks. After 12 weeks, blood samples and the liver were collected for biochemical analysis. Results. The induction of prediabetes resulted in increased release of liver enzymes (AST and ALT), increased liver glycogen and triglyceride, lipid peroxidation, and decreased sterol regulatory element-binding protein (SREBP1c) and antioxidant enzymes. However, the administration of BA decreased liver enzyme concentrations, decreased hepatic oxidative stress, and improved antioxidant enzymes such as SOD and GPx. Conclusion. BA administration improved liver function in diet-induced prediabetic rats in the presence or absence of dietary intervention.